(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
In the Minister of Home Affairs Regulation Number 20 Year 2018 concerning Village Financial Management, it is stated that village finance is all village rights and obligations that can be valued with money and everything in the form of money and goods related to the implementation of village rights and obligations. The purpose of this study was to find out the village financial management in Tompaso Village II, Tompaso Subdistrict, Minahasa District. The method of approach that is suitable for use in this study is a qualitative method. Data collection techniques used were interviews, observation and documentaries. Based on the results of the research and discussion, the authors draw conclusions regarding Village Financial Management in Tompaso II Village, Tompaso Subdistrict, Minahasa District, seen from the four stages of the government financial management cycle, namely: (1) Planning and Preparation (2) Ratification, (3) Implementation, ( 4) Reporting and evaluation. Suggestions that can be given are Planning and Preparation, Ratification, Implementation of the Village APB needs to be improved in quality and APB Village Reporting and Evaluation should be truly in accordance with the facts. Keywords: Management, Finance, Village.